Altered Mental Status: Epilepsy, Acute Psychosis, Intoxication or Delirium Tremens? - Shannon Toohey (eScholarship Publishing, University of California, 2016)
Audience: This simulation session can be used for emergency medicine residents or medical students, but it may be more appropriate for senior residents. Junior residents and medical students may also misdiagnose delirium tremens as a seizure disorder. Introduction: Delirium tremens (DT) is a rare, severe form of withdrawal that includes tremors, seizures, fever and delirium and occurs in approximately 5% of patients with alcohol withdrawal. Early identification and prompt treatment is essential as DT has a 5%-20% mortality rate which can be reduced to 1%-5% with appropriate therapy. Objectives: At the end of this simulation session the learner will: 1) Recognize signs and symptoms of delirium tremens (DT); 2) promptly treat DT with benzodiazepines and supportive care; 3) appropriately manage a patient with DT and effectively communicate with nurses and other team members during the resuscitation of an acutely ill patient. Method: This educational session is a high-fidelity simulation.